PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING DALAM SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK PADA SDN DUREN SAWIT JAKARTA - Paryanti, Atik Budi; Sumarsid, Sumarsid (JURNAL ILMIAH M-PROGRESS, 2022)
In the assessment or selection of the best teachers in SDN Duren Sawit Jakarta there are still some obstacles or problems such as the assessment of each teacher is still done manually, namely the principal must fill in the assessment instrument form every teacher has provided, which causes the assessment process to be less accurate and inefficient . In addition, to obtain or know information on the results of the selection of the best teachers requires quite a long time, because the administration section must re-enter the value of each teacher into Microsoft Excel and make prankingan teacher grades manually. Data collection methods used are interviews, observation and study of literature. The decision making method used by the author is Simple Additive Weighting (SAW), while the system development method used is the SDLC method with flowchart design tools, UML (Unified Modeling Language) and LRS (Logical Relational Structure). The program implementation uses PHP programming language with MySQL database. Decision support systems can be used to make it easier for schools to manage data, present information, produce reports and reduce errors in calculating grades and get accurate teacher ranking results and the application of the SAW method can improve the quality of decision making in the selection of the best teachers.Â Keywords : Implementation, Simple Additive Weighting, SPK, Selection Best Teacher